Altered cognitive function in systemic lupus erythematosus and associations with inflammation and functional and structural brain changes. Issue 7 (12th April 2019) - Barraclough, Michelle; McKie, Shane; Parker, Ben; Jackson, Alan; Pemberton, Philip; Elliott, Rebecca; Bruce, Ian N
Abstract : Objectives: Cognitive dysfunction (CD) is common in systemic lupus erythematosus (SLE) but the cause remains unclear and treatment options are limited. We aimed to compare cognitive function in SLE and healthy controls (HCs) using both behavioural and neuroimaging techniques. Methods: Patients with SLE with stable disease and HCs were recruited. Clinical and psychological data were collected along with a blood sample for relevant biomarkers. Neurocognitive function was assessed using tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB) and functional magnetic resonance imaging (fMRI) was used to examine brain responses to working memory (WM) and emotional processing (facial emotional recognition task, FERT) tasks. Results: Compared with HCs (n=30), patients with SLE (n=36) scored higher on measures of depression, fatigue and had higher hsCRP (p=0.013), IL-6 (p=0.003) and B lymphocyte stimulator (p<0.001). Patients with SLE had poorer performance on a task of sustained attention (p=0.002) and had altered brain responses, particularly in default mode network (DMN) regions and the caudate, during the WM task. Higher organ damage and higher VCAM-1 were associated with less attenuation of the DMN (p=0.005 and p=0.01, respectively) and lower BOLD signal in the caudate areas (p=0.005 and p=0.001, respectively). Increased IL-6 was also associated with lower BOLD signal in caudate areas (p=0.032). Conclusions: Sustained attention was impaired in patients with SLE. Poor attenuation of the DMN may contribute to cognitive impairments in SLE and our data suggest that in addition to mood and fatigue inflammatory mechanisms and organ damage impact cognitive functioning in SLE. The multifaceted nature of CD in SLE means any therapeutic interventions should be individually tailored.